2023
DOI: 10.1002/esp.5724
|View full text |Cite
|
Sign up to set email alerts
|

Inundation and flow properties of a runoff‐generated debris flow following successive high‐severity wildfires in northern Arizona, USA

Alexander N. Gorr,
Luke A. McGuire,
Ann M. Youberg
et al.

Abstract: Burned slopes are susceptible to runoff‐generated debris flows in the years following wildfire due to reductions in vegetation cover and soil infiltration capacity. Debris flows can pose serious threats to downstream communities, so quantifying variations in flow properties along debris‐flow runout paths is needed to improve both conceptual and quantitative models of debris‐flow behaviour to help anticipate and mitigate the risk associated with these events. Changes in flow properties along the runout paths of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 93 publications
0
0
0
Order By: Relevance
“…Liu et al (2016), O'Brien and Julien (1988), and O'Brien et al (1985, 1993. The VC range was established based on the uncertainty in the volume of debris flow deposits observed by Gorr et al (2024) and the hydrograph simulations (Figure 2). Manning's n values were selected to cover a broad spectrum from 0.03 to 0.1 m s 1/3 , which align with the conventional values attributed to barren terrains and mixed forests, and are similar to those calibrated in recently burned watersheds in the Earth's Future 10.1029/2023EF004318…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Liu et al (2016), O'Brien and Julien (1988), and O'Brien et al (1985, 1993. The VC range was established based on the uncertainty in the volume of debris flow deposits observed by Gorr et al (2024) and the hydrograph simulations (Figure 2). Manning's n values were selected to cover a broad spectrum from 0.03 to 0.1 m s 1/3 , which align with the conventional values attributed to barren terrains and mixed forests, and are similar to those calibrated in recently burned watersheds in the Earth's Future 10.1029/2023EF004318…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Postfire debris flow volume models have been developed in the western USA and Australia (Gartner et al, 2014;Nyman et al, 2015;Santi & Morandi, 2013;Wall et al, 2023) while PFDFs have been reported much more broadly (e.g., Conedera et al, 2003;Esposito et al, 2023;Wang et al, 2022). Employing PFDF volume models outside regions where they were developed has been met with mixed results (Gorr et al, 2024;Nyman et al, 2015) and is likely to increase uncertainty associated with flow volume, a critical input for inundation models (Barnhart et al, 2021). An alternative approach to estimating inflow hydrographs for debris-flow runout modeling is the use of a bulking factor (e.g., Gusman et al, 2009).…”
Section: Benefits and Challenges Of The Prefire Approachmentioning
confidence: 99%
See 3 more Smart Citations